Making Eugenics a Public Issue: A Reception Study of the First German Compendium on Racial Hygiene, 1921-1940 - Fangerau, Heiner M. (Science & Technology Studies, 2005)
During the 1920s, the world-wide eugenics movement reached a peak level of popularity. Historians have stressed the key role of the textbook “Human Heredity and Racial Hygiene” in the popularisation of eugenic thinking in Germany. In this textbook the well known scientists Erwin Baur (1875-1933), Eugen Fischer (1874-1967) and Fritz Lenz (1887-1976) tried to combine genetics, anthropology and racial hygiene to form a “Magna Carta” of eugenics. This paper aims at quantitatively reconstructing the book’s development into a standard work. 325 contemporary reviews of the book were analysed. More than 80% of the reviewers evaluated the book positively recommending it to a variety of readers. Most of the reviewers were Medical Doctors concentrating on the eugenic aspects of the book. The reception study makes the reciprocity of eugenics as an accepted science and academics forming it into science prevalent. Explanations for the uniform reaction of the scientific community are discussed. *Key words*: reception study, interwar years, eugenics